Aesthetic value - Goldman, Alan H. 1945- (Focus series, 1995)
In this concise survey, intended for advanced undergraduate students of aesthetics, Alan Goldman focuses on the question of aesthetic value, using many practical examples from painting, music, and literature to make his case. Although he treats a wide variety of views, he argues for a non-realist view of aesthetic value, showing that the personal element can never be factored out of evaluative aesthetic judgments and explaining why this is so.